ANALISIS AKTIVITAS BELAJAR PESERTA DIDIK MENGGUNAKAN MODEL PEMBELAJARAN INDEX CARD MATCH - Napsawati; Agustina Setyaningsih (Pendidikan Fisika UIN Alauddin Makassar, 2022)
One of the subjects that requires a fun learning model is the Science Physics subject. This is because science is one of the subjects considered difficult by students. To overcome these problems, various efforts have been made by the teacher, one of which is through a fun learning model. One of the learning models that can create a pleasant learning atmosphere is the Index Card Match learning model. This study aims to analyze the learning activities of students through the application of the Index Card Match learning model. The type of research used is a descriptive type of pre-experimental research with a One Shot Case Study design. The research was carried out at MTs DDI Sepange. The subjects of this study were class IX students in the 2019/2020 academic year as many as 24 people. The research instrument is an observation sheet and a questionnaire sheet. Based on the research that has been obtained, it shows that there is an increase in student learning activities after the implementation of the index card match learning model because the learning atmosphere created is able to increase student interest in the learning model, so the index card match learning model can be used as an alternative to increase student learning activities in learning science physics.